IMPLEMENTASI REKAM MEDIS ELEKTRONIK (RME) RAWAT JALAN DI RSUD TOTO KABILA BONE BOLANGO - Fassyalina Khayla Badu; Moh Ichsan Arifin Antu; Riska Ahmad (MOTORIK Jurnal Ilmu Kesehatan, 2025)
The implementation of electronic medical records (EMR) as a computerized health information system has become a strategic focus in modernizing hospitals in Indonesia. RSUD Toto Kabila Bone Bolango has adopted this system for outpatient services since early 2025. However, the implementation process still faces several challenges, including limited network infrastructure, uneven staff training, high dependence on IT teams, data input errors, and suboptimal system utilization by medical personnel. This study aims to explore the implementation of EMR at RSUD Toto Kabila and analyze its impact on service efficiency and healthcare worker readiness. The research used a qualitative approach with phenomenological methods and triangulation techniques, including interviews, observation, and documentation. Conducted from April to June 2025, the study involved seven informants: the head of the medical record unit, IT staff, and outpatient medical personnel. The findings show that EMR implementation has had a positive impact on service efficiency, workflow acceleration, and reduced reliance on paper-based records. Nevertheless, structural issues such as unstable connectivity and competency gaps among professions hinder optimal system use. Strategic improvements in cross-professional training and digital culture reinforcement are needed to ensure the sustainability of electronic health information systems in healthcare facilities.